FOTODEGRADASI ZAT WARNA TEKSTIL METHYLENE BLUE DAN CONGO RED MENGGUNAKAN KOMPOSIT ZnO-AA DAN SINAR UV - Diantariani, Ni Putu; Suprihatin, Iryanti Eka; Widihati, Ida Ayu Gede (Jurnal Kimia (Journal of Chemistry); Vol. 10, No. 1 Januari 2016DO - 10.24843/JCHEM.2016.v10.i01.p18, 2016)
Research on  photodegradation of textile dyes  of methylene blue (MB) and congo red (CR) using ZnO-Activated Carbon composite and ultraviolet (UV) light has been done. This research included synthesis zinc oxide (ZnO), synthesis ZnO-Activated Carbon, and the application of composite to degrade textile dyes of MB and CR. In this research studied the effect of pH, concentration and time of UV radiation  towards photodegradation percentages  of dyes. Then it determined the rate and the effectivity of photodegradation of MB and CR dyes using ZnO-Activated Carbon composite. The result showed that  photodegradation of MB reach optimal condition at pH 11 with radiation time 4 hour, whereas CR is at pH 5 with the same radiation time. The more initial concentration of MB and CR applicated, the lower of photodegradation percentages. Constanta of photodegradation rate of MB and CR dyes using ZnO-Activated Carbon composite are 0.8316 and 1.4938 hour-1 respectively. ZnO-Activated Carbon composite as a photocatalyst can degrade effectively MB and CR dyes with photodegradation percentages of 99.40±0.23 % and 99.61±0.24% respectively.
Keywords: ZnO-Activated Carbon composite, photodegradation, methylene blue, congo red